Desain Pengembangan Hybrid Bidirectional Inverter 1500 Watt Dengan Menggabungkan Energi Alternatif Pembangkit Listrik Tenaga Surya Dan Energi Utilitas Untuk Aplikasi Rumah Tangga - Hendri Hendri; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Solar power plant ( SPP ) is an alternative energy which is currently undergoing development but the use of solar power utilization is not optimal due to the intensity of sunlight in Indonesia is only about 5 hours a day . To optimize the use of solar power is so in this paper will be discussed about the development of hybrid bidirectional inverter 1500 Watt design that combines alternative energy solar power plant ( SPP ) with the energy utilities. Hybrid bidirectional inverter can work both ways , namely as inveter and as a rectifier so as to make solar power as a primary energy and energy utilities as secondary energy . In this paper also discusses how much value the efficiency of electric power saving that can be given by this hybrid system in household applications.Keywords : Hybrid Bidirectional Inverter, Alternative Energy, PLTS, SPWM, Household Applications.